2022
DOI: 10.1007/s00520-022-07405-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral and dental late effects in long-term survivors of childhood embryonal brain tumors

Abstract: Purpose To investigate oral and dental late effects in survivors of childhood brain tumors medulloblastoma (MB) and central nervous system supratentorial primitive neuroectodermal tumor (CNS-PNET). Methods This cross-sectional study assessed oral and dental late effects in MB/CNS-PNET survivors treated before 20 years of age, and with a minimum of 2 years since treatment. Participants went through an oral and radiographic examination. We assessed oral stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Regarding the type of study, 15 were cohort studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], 13 case–control studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], and 7 cross-sectional studies [ 3 , 4 , 15 , 16 , 25 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the type of study, 15 were cohort studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], 13 case–control studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], and 7 cross-sectional studies [ 3 , 4 , 15 , 16 , 25 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several points were considered in the case definition setting. Some studies addressed multiple topics: 24 assessed caries incidence [ 4 , 15 , 17 , 22 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 36 , 37 , 39 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 ], 18 assessed dental abnormalities such as root stunting and microdontia [ 4 , 16 , 18 , 20 , 21 , 23 , 26 , 27 , 29 , 39 , 40 , 41 , 43 , 44 , 46 , 47 , 48 ], and 15 stressed the developmental defects of enamel [ 16 , 17 , 21 , 23 , 26 , 27 , 29 , 30 , 36 , 40 , 41 ,…”
Section: Resultsmentioning
confidence: 99%
“…However, the percentage of the latter was low. Previous studies have shown that dental development defects, including microdontia, oligodontia, hypodontia, enamel defects, and root malformations, can occur in CCS (Kilinc et al 2019;Tanem et al 2022;Halperson et al 2022;Seremidi et al 2023). The prevalence of these defects may depend on the type of cancer and the treatment received.…”
Section: Discussionmentioning
confidence: 99%